Self-Assessment among Young Learners of English - Arni Sukmiarni (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2015)
The implementation of self-assessment among young learners becomes a challenging issue to include in English classroom assessment. The common belief that children cannot self-assess accurately as adults do seems to yield that the inclusion of self-assessment in TEYL is still not prevalent yet. Self-assessment is an assessment involving the ability in assessing one’s own performance in learning. This is strongly related to one’s metacognition development. The tendency of earlier research investigating metacognitive capacities of young children concludes that mecognition in children is a late developing skill (Lai, 2011). In fact, more recent empirical studies conclude that young children have capability of simple metacognition thought (Lai, 2011). Hence, the inclusion of self-assessment in TEYL can be implemented as an assessment supporting other assessment conducted in classroom. Self-assessment is beneficial in improving students’s own awareness of their learning progress. In Indonesian context, English as a foreign language, has been taught in elementary school since 1994 and generally formative and summative assessments as classroom assessments are employed to assess student’s progress in learning. Self-assessment is an assessment that needs to be considered to include in classroom assessment. This paper discusses self-assessment among young learners, in this context elementary school students studying English.